Caracterización morfológica de las malezas del género Leptochloa - Peña Simbaña, Daniel Josue (2022)
The genus Leptochloa consists of about forty species and its center of distribution is located within the subtropical and warm regions of the world. However, its variety has developed dramatically outside these regions, thanks to human activity (agriculture and exchange of seeds and plant webs). The genus Leptochloa has a magnificent dispersal potential due to the convenience of spikelet disarticulation, which occurs with the slightest friction or movement of the plant, and the enormous amount of fruit that can be generated. The information obtained was carried out by means of the technique of analysis, synthesis and summary, with the purpose of informing the reader about the morphological characterization of the weeds of the genus Leptochloa. From the above detailed it was determined that the important weed species of the genus Echinochloa are: Leptochloa filiformis. Leptochloa chinensis, Leptochloa chloridiformis, Leptochloa uninervia, Leptochloa panicea and Leptochloa virgata, which can reduce crop yields due to direct competition for nutrients, water, light and space. For the management of weed species of the genus Leptochloa spp. there are several alternatives such as cultural and chemical practices that favor the management and control of Leptochloa spp. The herbicides profoxydim (AURA-Basf) and cyhalofop butyl (CLlNCHER-Dow Agrosciences) effectively control Leptochloa spp. when the weed has 1-2 leaves.